How to increase COVID-19 vaccine uptake among children? determinants associated with vaccine compliance - Moshe Hoshen; Moshe Hoshen; Vered Shkalim Zemer; Vered Shkalim Zemer; Shai Ashkenazi; Zachi Grossman; Zachi Grossman; Maya Gerstein; Maya Gerstein; Noga Yosef; Moriya Cohen; Herman Avner Cohen; et al. (Frontiers Media S.A., 2023)
ObjectiveThree aims: to elucidate determinants associated with COVID-19 vaccine uptake in children and the association with parental vaccination; to compare rates of PCR-positive SARS-CoV-2 results between vaccinated and unvaccinated children; to estimate the rate of parental COVID-19 vaccination and its association with the vaccination rate of their children.MethodsWe performed a retrospective chart review of all children aged 5-11 years registered at a central district in Israel from November 21st, 2021 to April 30th, 2022, and characterized COVID-19 vaccinated vs. unvaccinated individuals. Data retrieved from the electronic medical files included: demographics [age, gender, sector, socioeconomic status (SES)]; COVID-19 vaccination (first and second doses) and influenza vaccination status; co-morbidities; and parental vaccinations for COVID-19. We divided the population into three distinct demographic groups: non-ultra-orthodox Jews (43,889 children), ultra-orthodox Jews (13,858 children), and Arabs (4,029 children).ResultsOf the 61,776 children included in the study, 20,355 (32.9%) received at least one dose of the COVID-19 vaccine. Vaccination rates were similar amongst males and females and were higher in children aged 9-11 years compared to children aged 5-6 years. Multivariate analysis identified five independent determinants that were significantly (p < 0.001) associated with low vaccination rates: Arab and ultra-orthodox sectors (odds ratios: 0.235 and 0.617, respectively); children aged 5-8 years; children of low SES; and children who had not received previous seasonal influenza vaccination. Relatively high vaccination rates were noted amongst children with the following medical co-morbidities: treatment with biological agents (42.9%); solid tumor transplantation (42.9%); type 1 diabetes mellitus (38.5%), asthma (38.2%), and attention deficit and hyperactivity disorder (ADHD) (37.6%). Regarding the uptake of two vaccine doses among children with co-morbidities, it was highest in those with type 1 diabetes mellitus, heart failure, treatment with biological agents, asthma and obesity.ConclusionThis study highlights several pediatric sub-populations with low and high vaccine uptake. It is essential to focus on determinants associated with low vaccination rates.